2015
DOI: 10.1371/journal.pone.0130839
|View full text |Cite
|
Sign up to set email alerts
|

Implication of Leptin-Signaling Proteins and Epstein-Barr Virus in Gastric Carcinomas

Abstract: We investigated the clinicopathological implications of leptin-signaling proteins and Epstein-Barr virus (EBV)-infection status in gastric carcinomas. Immunohistochemistry for leptin signalling-related proteins (leptin, leptin-receptor, pSTAT3, ERK, pAkt, mTOR and HIF-1 alpha), and in situ hybridization for EBV-encoded small RNAs was performed in 343 cases of gastric carcinomas. The siRNA against leptin-receptor was transfected into three stomach cancer cell lines, and western blot for caspase 3 was performed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…These studies were published between 2004 and 2015. In all included studies, 1 study 27 was conducted in America populations, and others were conducted in Asian populations, including 3 studies from Japan, 24 , 26 , 38 4 from Korean, 28 29 , 35 , 41 and 15 from China. 18 , 25 , 30 – 34 , 36 37 , 39 – 40 , 42 – 45 The total number of patients was 2872, with a median number of 98 patients each study (range: 50–343).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies were published between 2004 and 2015. In all included studies, 1 study 27 was conducted in America populations, and others were conducted in Asian populations, including 3 studies from Japan, 24 , 26 , 38 4 from Korean, 28 29 , 35 , 41 and 15 from China. 18 , 25 , 30 – 34 , 36 37 , 39 – 40 , 42 – 45 The total number of patients was 2872, with a median number of 98 patients each study (range: 50–343).…”
Section: Resultsmentioning
confidence: 99%
“…In 11 included studies, 25 , 27 , 33 , 36 37 , 39 – 40 , 42 – 45 p-stat3 expression was quantified according to the percentage of positive cells and staining intensity. In other 12 included studies, 18 , 24 , 26 , 28 32 , 34 – 35 , 38 , 41 p-stat3 expression was quantified according to the percentage of positive cells alone. In most studies, the positive staining of p-stat3 was located in nucleus, others located in nucleus and cytoplasm 26 , 36 , 40 , 30 , 33 , 44 All included studies reported the association between p-stat3 expression and clinicopathological characteristics, and 11 studies reported data on the effect of p-stat3 expression on overall survival.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to gastric carcinoma Ob-R expression was correlated with poor survival in 47% of patients with lymph node metastasis, 60% of the patients with advanced gastric cancer, and 41% of the cases defined as Lauren diffuse pathology [103] (Table 1). Of note, gastric cancer has been classified in many different ways such as Lauren, World Health Organization (WHO), and Borrmann classifications [104].…”
Section: Leptin and Tumor Behavior Of The Gastrointestinal Tractmentioning
confidence: 99%
“…For instance, preclinical evidence has revealed that leptin stimulates esophageal, colorectal, prostate and breast cancer cell proliferation [62-66] and is responsible for the association between diabetes and prostate cancer [67]. The leptin-receptor might predict poor prognosis in patient with advanced gastric cancer (AGC) [68]. In addition, a pooled analysis from three cohorts by Stolzenberg-Solomon et al supports an relationship between enhancing leptin levels and pancreatic cancer [69].…”
Section: Leptinmentioning
confidence: 99%